Does Neurosurgery Residency Training Program Meet the Current Clinical Practice Needs? Results of an Online Questionnaire-Based Survey of Alumni - Nagesh, Madhusudhan; Sadashiva, Nishanth; Tyagi, Gaurav; Shashidhar, Abhinith; Konar, Subhas; Prabhuraj, Andiperumal; Vazhayil, Vikas; Pruthi, Nupur; Arimappamagan, Arivazhagan; Shukla, Dhaval (Indian Journal of Neurosurgery, 2025)
Neurosurgery as a specialty is evolving daily, and new subspecialties are emerging. New treatment modalities are incorporated into day-to-day practice. The present residency training program must be remodeled to meet current needs. The objective of the study was to evaluate whether the institute's residency training program met the needs of the current practice of the alumni of the institute.An online questionnaire-based survey was prepared considering the themes of the residency program, subspecialty exposure, and fellowships. The links were forwarded to the institute's alumni from 2003 to 2021 batches, and the responses were analyzed.In total, 102 responses were received (85% response rate). Ninety-two respondents practice within the country, most at private multispecialty hospitals. In all, 92.2% were satisfied with the overall training they received; most deemed it adequate for their current clinical practice. Satisfaction levels were low for training on surgical anatomy, follow-up assessments, and multidisciplinary interactions. Exposure to subspecialties like endovascular was the least, and exposures to spine, functional, endoscopic skull base, and radiosurgery were deemed subpar. Forty-eight pursued additional fellowships in various specialties, and 85.4% reported that the fellowship significantly contributed to their current practice.Transition from residency to individual practice is often challenging for young neurosurgeons. This survey highlights the expectations and satisfaction levels of the alumni. It also emphasizes the need for exposure to upcoming subspecialties.
Keywords: neurosurgical residency; residency training program; fellowship; subspecialty training